2019
DOI: 10.1038/s41574-018-0137-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplant diabetes mellitus in patients with solid organ transplants

Abstract: Solid organ transplantation (SOT) is an established treatment for patients with end-organ disease. SOT is also a life-saving procedure although kidney failure patients may survive with dialysis treatment. However, transplantation is accompanied by associated cardiovascular risk factors, and post-transplant diabetes mellitus (PTDM) is one of the most important ones. PTDM develops in 10-20% of kidney transplanted patients and in some 20-40% of other SOT patients. PTDM patients have twice as high mortality as oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
186
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(196 citation statements)
references
References 187 publications
6
186
2
2
Order By: Relevance
“…These results are in accordance with those provided by Ye et al [5], where cumulative rates of PTDM were 11.1, 32.0 and 38.4% after 12-, 24-and 36-months post HT respectively [5]. With the documented time-dependent increase in incidence of PTDM after HT, it is clear that other factors in addition to glucocorticoids, in particular CNIs, are involved in its pathogenesis, and that this entity differs from steroid DM [30]. CNIs decrease insulin release by direct toxic effect on pancreatic β-cells.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in accordance with those provided by Ye et al [5], where cumulative rates of PTDM were 11.1, 32.0 and 38.4% after 12-, 24-and 36-months post HT respectively [5]. With the documented time-dependent increase in incidence of PTDM after HT, it is clear that other factors in addition to glucocorticoids, in particular CNIs, are involved in its pathogenesis, and that this entity differs from steroid DM [30]. CNIs decrease insulin release by direct toxic effect on pancreatic β-cells.…”
Section: Discussionsupporting
confidence: 91%
“…PTDM is an important risk factor for solid organ transplant recipients and is strongly associated with mortality and graft loss in recipients 4,8 . Currently, the reasonable first step for prevention of PTDM is assessment and elimination of the risk factors for patients with high‐risk diabetes after transplantation 27 . A randomized controlled trial indicated that new‐onset diabetes after transplant (NODAT) was reported to occur in 33.6% of organ recipients with the use of tacrolimus, higher than the percentage observed with cyclosporin A (26.0%, P < .05) 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus is an important risk factor for PTDM, similar to family history of diabetes, central obesity, and impaired fasting blood glucose. The recipients with these risk factors are more likely to develop PTDM 27,28 . However, in some conditions, it is obviously difficult to remove these risk factors, while tacrolimus might also be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…PTDM is characterized by a combination of insulin resistance and decompensated insulin release, which is similar to type 2 DM (22). Various risk factors including unmodifiable (i.e., older age, genetic background, family history of DM) and modifiable (i.e., central obesity, immunosuppressive agents, hepatitis C infection, and smoking) risk factors have been implicated for the development of PTDM in previous studies (8,23,24).…”
Section: Discussionmentioning
confidence: 99%